Growth factor stimulation of cardiomyocytes induces changes in the transcriptional contents of secreted exosomes. Issue 1 (17th May 2013) - Gennebäck, Nina; Hellman, Urban; Malm, Linus; Larsson, Göran; Ronquist, Gunnar; Waldenström, Anders; Mörner, Stellan
Abstract : Exosomes are nano‐sized extracellular vesicles, released from various cells, which can stimulate or repress responses in targets cells. We recently reported that cultured cardiomyocytes are able to release exosomes and that they, in turn, are involved in facilitating events in target cells by alteration of gene expression. We investigated whether external stimuli of the cardiomyocyte might influence the transcriptional content of the released exosomes. Exosomes were isolated from media collected from cultured cardiomyocytes (HL‐1) with or without growth factor treatment (TGF‐β2 and PDGF‐BB), with a series of differential centrifugations, including preparative ultracentrifugation and separation with a sucrose gradient. The exosomes were characterized with dynamic light scattering (DLS), electron microscopy (EM) and Western blot and analyzed with Illumina whole genome microarray gene expression. The exosomes were rounded in shape and had an average size of 50–90 nm in diameter with no difference between treatment groups. Analysis of the mRNA content in repeated experiments conclusively revealed 505 transcripts in the control group, 562 in the TGF‐β2‐treated group and 300 in the PDGF‐BB‐treated group. Common transcripts (217) were found in all 3 groups. We show that the mode of stimulation of parental cells affects the characteristics of exosomes released. Hence, there is a difference in mRNA content between exosomes derived from cultured cardiomyocytes stimulated, or not stimulated, with growth factors. We also conclude that all exosomes contain a basic package consisting of ribosomal transcripts and mRNAs coding for proteins with functions within the energy supply system.